Educated - Westover, Tara (London : Hutchinson ; Penguin Books, 2018)
Tara Westover was seventeen the first time she set foot in a classroom. Born to survivalists in the mountains of Idaho, she prepared for the end of the world by stockpiling home-canned peaches and sleeping with her "head-for-the-hills bag." In the summer she stewed herbs for her mother, a midwife and healer, and in the winter she salvaged in her father$1 (Bs junkyard. Her father distrusted the medical establishment, so Tara never saw a doctor or nurse. Gashes and concussions, even burns from explosions, were all treated at home with herbalism. The family was so isolated from mainstream society that there was no one to ensure the children received an education, and no one to intervene when an older brother became violent. When another brother got himself into college and came back with news of the world beyond the mountain, Tara decided to try a new kind of life. She taught herself enough mathematics, grammar, and science to take the ACT and was admitted to Brigham Young University. There, she studied psychology, politics, philosophy, and history, learning for the first time about pivotal world events like the Holocaust and the Civil Rights Movement. Her quest for knowledge transformed her, taking her over oceans and across continents, to Harvard and to Cambridge University. Only then would she wonder if she$1 (Bd traveled too far, if there was still a way home.s
Choose the good -- The midwife -- Cream shoes -- Apache women -- Honest dirt -- Shield and buckler -- The Lord will provide -- Tiny harlots -- Perfect in his generations -- Shield of feathers -- Instinct -- Fish eyes -- Silence in the churches -- My feet no longer touch Earth -- No more a child -- Disloyal man, disobedient heaven -- To keep it holy -- Blood and feathers -- In the beginning -- Recitals of the fathers -- Skullcap -- What we whispered and what we screamed -- I$1 (Bm from Idaho -- A knight, errant -- The work of sulphur -- Waiting for moving water -- If I were a woman -- Pygmalion -- Graduation -- The hand of the almighty -- Tragedy then farce -- A brawling woman in a wide house -- Sorcery of physics -- The substance of things -- West of the sun -- Four long arms, whirling -- Gambling for redemption -- Family -- Watching the buffalo -- Educated.s
Biography
ENH
Keywords: Westover, Tara -- Family; Survivalism -- Idaho -- Biography; Women -- Idaho -- Biography; Victims of family violence -- Idaho -- Biography; Adult children of dysfunctional families -- Idaho -- Biography; English language